Pengaruh Viral Marketing, Harga Dan Kualitas Produk Terhadap Keputusan Pembelian Skincare Serum Wajah Implora (Studi Kasus Pada Mahasiswi Universitas Panca Marga) - Rheina Cindyta Nur Azizah; Joni Hendra; Tumini Tumini (JUMAD : Journal Management, Accounting, & Digital Business, 2024)
Research aims to see effect of viral marketing, price, and product quality on purchase decision partially. The type of research used is quantitative and a causal approach. The respondents were 103 female students of Panca Marga University who bought and used Implora facial serum between January - December 2022. The sampling technique used was non-probability sampling and purposive sampling method. The sample was 52 female students who fulfilled the research measures. Data analysis techniques used test validity, reliability, classical assumptions, multiple linear analysis, determination coefficient, and hypothesis testing. The results of the partial tests that have been carried out see that viral marketing variables have a positive and significant effect on purchase decisions for Implora facial serum skincare, price has a positive and significant effect on purchase decisions for Implora facial serum skincare, and product quality has a positive and significant effect on purchase decisions for Implora facial serum skincare.